2020
DOI: 10.5173/ceju.2020.0087
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the urological practice: changes and future perspectives

Abstract: Introduction The COVID-19 pandemic has brought great challenges to the management of urological patients. Like most surgical specialties, urology has shifted towards an emergency mentality. Currently, the beginning of the de-escalation phase of the pandemic has been observed, which will certainly pose new challenges to the urological community. Material and methods A non-systematic search was conducted through the Medline and Web of Science databases. The main keywords … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The COVID-19 pandemic brought about significant disruption. Internships at healthcare institutions in Singapore had to be canceled, as with health-related internships or clinical attachments elsewhere (Wall, 2020;Ahmed et al, 2020;La Republicca, 2020;Nowak et al, 2020). Interestingly, Bugis (2020) reported that 60.2% of health organizations (mostly PH HESWBL 12,3 organizations) continued with on-site internships between March to May 2020 with "limited COVID-19 restrictions" applied, citing reasons such as reduced workforce capacity, involvement of interns in COVID-19-related work, and how a virtual internship was not amenable.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic brought about significant disruption. Internships at healthcare institutions in Singapore had to be canceled, as with health-related internships or clinical attachments elsewhere (Wall, 2020;Ahmed et al, 2020;La Republicca, 2020;Nowak et al, 2020). Interestingly, Bugis (2020) reported that 60.2% of health organizations (mostly PH HESWBL 12,3 organizations) continued with on-site internships between March to May 2020 with "limited COVID-19 restrictions" applied, citing reasons such as reduced workforce capacity, involvement of interns in COVID-19-related work, and how a virtual internship was not amenable.…”
Section: Discussionmentioning
confidence: 99%